Harmonic Reveries: The Intercultural Signifiance of Lear Dreaming - Tan, Marcus (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2015)
Lear Dreaming (2012) is an offspring of, and sequel to, the (in)famous multi-cultural pan-Asian collage Lear (1997), in which director and creator Ong Keng Sen employed a diversity of Asian performance traditions to reimagine and reconceive Shakespeare’s tragedy. The soundscape of Lear Dreaming reverberates with the (dis)harmonies and dissonance of electronic synth sounds, gamelan music, pipa songs and Korean jeongak; it places modernity, tradition, contemporaneity and custom in auditory confrontation. With only one actor surrounded by eight musicians, this acoustic interplay is further interjected with the oral patterns of Noh speech, the musicality of Mandarin Chinese and sonorities of Bahasa Indonesia. As a piece of postdramatic “music theatre”, I demonstrate how Lear Dreaming advances intercultural theatrical practice as a sonic performative. In its interplay of Asian performance cultures in/as sonic space, the production posits an alternative performative mode where the intercultural is the acoustic. This paper critically examines the acoustic strategy employed by Ong and analyses the soundscape of Lear Dreaming – the harmonies, harmonics, distortions and discordance – to consider issues of signification, representation, signifiance and the sublime in the performance of Asian inter-culturalisms.